2007
DOI: 10.1016/j.bbamem.2007.04.012
|View full text |Cite
|
Sign up to set email alerts
|

Ouabain activates signaling pathways associated with cell death in human neuroblastoma

Abstract: Cardiotonic steroids (CTS) like ouabain are not only specific inhibitors of the sodium pump (Na(+),K(+)-ATPase), they also can influence various cytosolic signaling events in a hormone-like manner. In the neuroblastoma cell line SH-SY5Y ouabain triggers multiple signaling pathways. Within 30 min of incubation with 1 or 10 microM ouabain, SH-SY5Y cells generate reactive oxygen species to a level approximately 50% above control and show a modest but significant elevation in cytosolic [Ca(2+)] of about 25%. After… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
61
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(73 citation statements)
references
References 64 publications
11
61
0
1
Order By: Relevance
“…*P Ͻ 0.05 vs. 10 ng/ml TRAIL-treated cells. (11,15). Consistently, we found ROS induction in response to ouabain treatment in H292 lung cancer cells, while TRAIL treatment caused only an insignificant effect on cellular ROS level.…”
Section: Ouabain Sensitizes H460 Human Lung Cancer Cells To Trailindusupporting
confidence: 84%
“…*P Ͻ 0.05 vs. 10 ng/ml TRAIL-treated cells. (11,15). Consistently, we found ROS induction in response to ouabain treatment in H292 lung cancer cells, while TRAIL treatment caused only an insignificant effect on cellular ROS level.…”
Section: Ouabain Sensitizes H460 Human Lung Cancer Cells To Trailindusupporting
confidence: 84%
“…In smooth muscle, HeLa, and neuroblastoma cells, ouabain induces apoptosis (22,23). In contrast, ouabain has an antiapoptotic effect in LLC-PK1 and kidney cells (24), preventing apoptosis induced through serum deprivation in renal proximal tubular rat cells (24).…”
Section: Resultsmentioning
confidence: 99%
“…Early epidemiologic studies by Stenkvist et al reported significantly lower mortality rates of cancer patients under cardiac glycoside treatment (25,26). Because then, numerous in vitro studies have reported potent antiproliferative effects of these compounds in a panel of cancer cell lines, including breast (27), prostate (28), melanoma (29), pancreatic (30), lung (31), leukemia (32), neuroblastoma (33), and renal adenocarcinoma (ref. 34; Table 2).…”
Section: Discussionmentioning
confidence: 99%